Galaxy Zoo: A Catalog of Overlapping Galaxy Pairs for Dust Studies - Keel, W; Manning, A; Holwerda, B; Mezzoprete, M; Lintott, C; Schawinski, K; Gay, P; Masters, K (2012)
Analysis of galaxies with overlapping images offers a direct way to probe the distribution of dust extinction and its effects on the background light. We present a catalog of 1990 such galaxy pairs selected from the Sloan Digital Sky Survey (SDSS) by volunteers of the Galaxy Zoo project. We highlight subsamples which are particularly useful for retrieving such properties of the dust distribution as UV extinction, the extent perpendicular to the disk plane, and extinction in the inner parts of disks. The sample spans wide ranges of morphology and surface brightness, opening up the possibility of using this technique to address systematic changes in dust extinction or distribution with galaxy type. This sample will form the basis for forthcoming work on the ranges of dust distributions in local disk galaxies, both for their astrophysical implications and as the low-redshift part of a study of the evolution of dust properties. Separate lists and figures show deep overlaps, where the inner regions of the foreground galaxy are backlit, and the relatively small number of previously-known overlapping pairs outside the SDSS DR7 sky coverage.